Basal inflection-control led shelf-edge wedges off New Jersey track sea-level fall - Gulick, S. P. S.; Goff, J. A.; Austin, J. A.; Alexander, C. R.; Nordfjord, S.; Fulthorpe, C. S. (Geology, 2005)
A key marker for examining the latest Pleistocene history of the New Jersey margin is the high-amplitude, long-recognized R-horizon reflector. This time-transgressive surface was formed 4733 ka and represents the integrated topographic and bathymetric surface developed during the complicated sea-level oscillation associated with the regression that preceded the Last Glacial Maximum (LGM). From landward to seaward across the outer shelf, the R reflector changes from subhorizontal, in most locations < 9 m beneath the modern seafloor, to seaward dipping, forming the base of two of flapping sediment wedges: the previously described outer-shelf wedge and a deep-shelf wedge seaward of it. This transition occurs across two inflection zones, where the dip of the R reflector steepens seaward, that can be traced for tens of kilometers along strike and mark the landward limits of these wedges. These inflection zones are possibly former wave-dominated shorefaces; these represent the primary topographic elements present during the last regression. We speculate that these inflections dictated both the locations for deposition of the two prograding, of flapping wedges that developed during the complex sea-level fall prior to the LGM and their successive erosion before and after the LGM. We suggest that such inflection zones and their associated wedges are important markers of regression in clastic-dominated outer-shelf settings along passive margins.
922awTimes Cited:19Cited References Count:24